PSYCHOPROPHYLAXIS EFFECT ON POSTPARTUM PERIOD - Natsiou, Konstantina (International Journal of Research -GRANTHAALAYAH, 2025)
Introduction: Psychoprophylaxis during pregnancy has been associated with favorable labor outcomes. Nevertheless, less is known about its effect on postpartum period, when mood disorders and lactation problems may occur. Aim: This narrative review refers to the effect of the psychoprophylaxis sessions during pregnancy on the postpartum period (puerperium) Methods: A literature review was conducted using the international databases Medline/PubMed, Scopus and Google Scholar. Only quantitative studies published in English language journals were included. Results: Few studies have explored the effect of psychoprophylaxis on puerperium. Psychoprophylaxis was positively associated with successful breastfeeding and negatively associated with maternity blues. Sample selection was a limitation in all three studies included in this review. Conclusions: Psychoprophylaxis may exert positive effects not only on labor outcomes, but also on post-partum period. Randomized control trials focusing especially on Lamaze method are necessary.